Microbial Plant Pathogens-Detection and Disease Diagnosis: Fungal Pathogens, Vol.1 - Narayanasamy, P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Plants are infected by different microbial pathogens, of which fungal pathogens form the highly evolved and earliest recognized group. The morphological, biological, biochemical and physiological characteristics have been used for the detection, identification and differentiation of fungal pathogens up to species level. Pathogenicity on a set of differential host plant species or crop cultivars has been useful for the identification of physiologic races existing within a morphologic species/variety. As the techniques based on the above mentioned characteristics require long time and yield inconsistent results, the need for the development of techniques with greater accuracy, reliability, reproducibility and capable of providing the results rapidly was realized. Immunoassays have been shown to be effective in detecting several fungal pathogens present in plants, planting materials, soil, water and air. Development of monoclonal antibody technology has greatly enhanced the sensitivity and specificity of detection, identification and differentiation of fungal species and varieties/strains. Nucleic acid-based techniques involving hybridization of probes with complementary sequences of the target pathogen(s) or amplification of specific sequences of the target pathogen DNA/fragment have been demonstrated to be the most efficient among the diagnostic techniques currently available. This volume provides exhaustive information on various methods of detection of fungal pathogens and the diagnosis of the diseases caused by them based on extensive literature search that will be useful to the researchers, teachers and graduate students of different disciplines of biological sciences, in addition to the extension pathologists, personnel of plant quarantines and certification programs. Presentation of a large number of protocols is a unique feature of this volume to facilitate selection of appropriate techniques for different investigations.
Chapter 1 Introduction -- 1.1 Microbial plant pathogens as a major limiting factor of crop production -- 1.2 Discovery of fungi as plant pathogens -- 1.3 Detection of fungal plant pathogens and disease diagnosis -- References -- Chapter 2 Detection of Fungal Pathogens in Plants -- 2.1 Detection of fungal pathogens in plant organs -- 2.2 Detection of fungal pathogens in seeds and planting materials -- Appendix -- References -- Chapter 3 Detection of Fungal Pathogens in the Environment -- 3.1 Detection of fungal pathogens in soil -- 3.2 Detection of fungal pathogens in water -- 3.3 Detection of fungal pathogens in air -- 3.4 Detection of fungal pathogens in alternative host plants -- Appendix -- References -- Chapter 4 Assessment of Variability in Fungal Plant Pathogens -- 4.1 Methods of assessment of variability in fungal pathogens -- 4.2 Assessment of variability in sensitivity to chemicals -- Appendix -- References -- Chapter 5 Diagnosis of Fungal Diseases of Plants -- 5.1 Choice of diagnostic tests for fungal pathogens -- 5.2 Agencies involved in disease diagnosis -- References.
Keywords: Life sciences; Microbiology; Plant diseases; Plant breeding; Entomology; Cytology -- Research_xMethodology.; Life Sciences; Plant Pathology; Microbiology; Plant Breeding/Biotechnology.; Entomology; Biological Techniques